NHS System Reform: Structural Changes - H Ravaghi (Tehran University of Medical Sciences, 2005)
The National Health Service (NHS) was established in 1948 to provide equitable healthcare for all citizens. Over the years the NHS has gone under different reforms and changes. In 2002 the NHS launched one of its biggest changes in structure since its commencement in 1948. The scale of these changes are greater than those established following the white paper "Working for Patients" in 1989 (Conservative Government) that indicated the introduction of the internal market (focus on efficiency). This review therefore proposes to give a brief summarize of the structural changes and current structure of the NHS in the England. The NHS plan was published in July 2000 (Labour Government) and outlined a 10 year plan of investment in the NHS. This delineates a vision for a service planned around the patients and more responsive to patients' needs. The Government emphasizes on the empowering of staff at all levels as a way to achieve this vision. "Shifting the Balance of Power" is part of the Government's plans for implementation of the NHS Plan and has directed to the establishment of new structures. The main feature of change has been giving locally based Primary Care Trusts the role of running the NHS and, with the local authorities, improving health in their areas. The PCTs are receiving 75% of the NHS budget to act as primary services provider, commissioner (service purchaser), network developer and controller. In addition, all former Health Authorities have been abolished and new Strategic Health Authorities (SHA) have been created to serve larger areas and with a more strategic role. The SHAs are responsible for developing strategic frameworks for the local health service; performance of the local health service; and building capacity in the local health service. The Department of Health is also refocusing to reflect these changes, including the abolition of its Regional Offices and relegating some of its operational responsibilities to SHAs and other organizations. While NHS Trusts (the organizations responsible for running most NHS hospitals, mental health and learning disability services, ambulance services and patient transport) continue to have the similar functions as before, they will have to create new working relationships with PCTs and SHAs. In addition Foundation Trust, which often referred 'Foundation Hospitals', were set up in April 2004 and are freestanding hospitals with greater autonomy within the NHS. New structures signify new relationships and partnerships both between NHS organisations and with other stakeholders. All NHS organisations locally - PCTs, Care Trusts and NHS Trusts - are now part of a single structure in which they are supposed accountable to SHAs, which are in turn accountable to Department of Health and ultimately to Secretary of State for Health. Relationships with other collaborators such as Local Authorities and voluntary organisations are also crucial, particularly for PCTs as they work towards improving health and integrating health and social care.